Sigil: Pengembangan e-modul berbasis realistik pada materi lingkaran untuk siswa kelas VIII SMP - Istikomah Istikomah; Riawan Yudi Purwoko; puji Nugraheni (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2020)
This study aims to produce a realistic e-module based on quality Sigil software that can be seen in terms of validity, practicality, and effectiveness. This research is a research and development, while the development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The instrument that will be used in this study are validation sheets, questionnaire student responses sheets, and test question. Data obtained from the study were then analyzed in terms of feasibility. The eligibility module, is allowed to be valid, effective and practical. In terms of validity, the average score given by media experts was 3,41 with the criteria “valid” while the realistic experts gave an average score of 3,00 with the criteria “valid”, and the material expert gave an average score for the learning scheme of e,69 with “valid” criteria. Based on practicality, the score given by students gets an average score of 83% with the criteria “very practical”. The effectiveness of the product can be seen from the percentage of completeness of the test scores that is obtained by 90% of all test subjects.Keywords: E-modules; Realistic Mathematics Education (RME); Circle; Sigil